Human Flourishing Across Cultures and Disciplines (Bloomsbury Publishing (UK), 2026)
What does it mean to flourish? This open access book serves as a call to action to reimagine and work towards a world where flourishing is a reality for all. An international team of scholars, practitioners, wisdom keepers, and policymakers come together to construct alternative visions of what a flourishing life could encompass. Their inclusive approach integrates indigenous wisdom, happiness, care, and storytelling and broadens our ideas of what it means to flourish. Where Western perspectives often emphasize individuality and wealth, here contributors look beyond individual achievement and material success as benchmarks of a successful life. Instead they foreground the intrinsic value of interpersonal relationships, community bonds, and spiritual fulfilment. Interweaving the threads of philosophical, scientific, indigenous, and political thought, they build a holistic understanding of human well-being and flourishing. We see how spiritual and metaphysical beliefs can coexist with scientific validity and contribute meaningfully to our understanding of human aspiration. A foreword from former Secretary-General of the United Nations Ban Ki-moon lays the groundwork for new attainable utopias that will help shape future Sustainable Development Goals. By encouraging us to rethink policies and our collective futures, this one-of-a-kind collection introduces us to a truly flourishing society where all dimensions of life are equally valued. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The New Institute.